2012
DOI: 10.2176/nmc.52.186
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Inhibits Angiogenesis In Vitro and Glioma Angiogenesis In Vivo in the Brain

Abstract: Antiangiogenic strategy is promising for malignant glioma. Histone deacetylase inhibitors (HDACIs) are unique anticancer agents that exhibit antiangiogenic effects. The in vitro and in vivo antiangiogenic effects of HDACIs, valproic acid (VPA), were investigated in malignant glioma in the brain. In vitro, VPA preferentially inhibited endothelial cell proliferation compared to glioma cell proliferation at the optimum concentration in a dose-dependent manner. VPA reduced vascular endothelial growth factor (VEGF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 30 publications
0
48
1
Order By: Relevance
“…The inhibiting rate of VPA group, DDP group and VPA+DDP group were as follows: 40.7%, 45.3%, 58% (as in B), they were significantly higher than control group (P<0.01). The cell cycle distribution changed in experimental group, the S-phase was decrease (as in C DOI:http://dx.doi.org/10.7314/APJCP.2012.13.8 Osuka et al, 2012). Based on our in vitro and in vivo data, we found that VEGF and MMP-9 were reduced but the expression of E-cadherin was increased after treated with VPA.…”
Section: Discussionmentioning
confidence: 72%
“…The inhibiting rate of VPA group, DDP group and VPA+DDP group were as follows: 40.7%, 45.3%, 58% (as in B), they were significantly higher than control group (P<0.01). The cell cycle distribution changed in experimental group, the S-phase was decrease (as in C DOI:http://dx.doi.org/10.7314/APJCP.2012.13.8 Osuka et al, 2012). Based on our in vitro and in vivo data, we found that VEGF and MMP-9 were reduced but the expression of E-cadherin was increased after treated with VPA.…”
Section: Discussionmentioning
confidence: 72%
“…VPA is also an HDACi (34,35) that has shown potent antitumor effects in vitro and in vivo in a variety of cancers, including GBM (36,37). This drug is a chromatin remodeling agent, consequently able to strongly modify gene expression (38-40), inducing cancer cell differentiation, apoptosis and growth arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have provided support to the hypothesis that valproic acid derivatives are a promising drug class for the treatment of GBM. Valproic acid attenuated the growth of glioma cells by inhibiting angiogenesis (48) and inducing differentiation (49). In addition, valproic acid increased the sensitivity of glioma cells to conventional GBM therapies, including TMZ and γ-radiation (50,51).…”
Section: Antipsychotics As Anti-gbm Therapeuticsmentioning
confidence: 99%